Human Rights in the Hungarian Labour Code - Szakats, Alexander (Victoria University of Wellington Law Review, 1998)
Protection of human rights, particularly the rights of persons working in the free market economy, features prominently in the Hungarian Labour Code enacted after the great political and economic change. As the state ceased to be the only, or the principal employer, either directly or in the guise of various "voluntary" cooperatives, the proliferation of private enterprises necessitated a law to regulate labour relations between the employers and employees. In this article Professor Szakats provides an overview of the Code by selecting certain provisions which emphasise human rights, and comparing them with the corresponding New Zealand statutory protection, and relevant ILO Conventions and Recommendations.